2023
DOI: 10.2147/copd.s396317
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effectiveness of Interventions to Promote Referral; Adherence; and Uptake of Pulmonary Rehabilitation for Patients with Chronic Obstructive Pulmonary Disease

Abstract: Background: Pulmonary rehabilitation (PR) is an effective treatment for patients with chronic obstructive pulmonary disease (COPD). However, referral, uptake, and adherence remain low. Objective: To determine effectiveness of interventions to increase patient referral, uptake, and adherence to PR programs for patients with COPD. Methods: Randomized controlled trials (RCTs), non-randomized controlled trials, pre-post studies, and uncontrolled studies were sought from 7 databases and 3 clinical trial registries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
(319 reference statements)
0
5
0
Order By: Relevance
“…To address this, the collection of data is vital [ 38 ]. Any results from collecting the data can be used to promote health equity by proposing where evidence-based changes are required in practices, policies and programmes [ 109 ], for example in adapting pulmonary rehabilitation to improve uptake and adherence in those least likely to attend [ 39 ]. As data on these characteristics have not been commonly collected, then any health inequalities among these characteristics cannot be identified or monitored and improvements cannot be made [ 104 , 109 111 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this, the collection of data is vital [ 38 ]. Any results from collecting the data can be used to promote health equity by proposing where evidence-based changes are required in practices, policies and programmes [ 109 ], for example in adapting pulmonary rehabilitation to improve uptake and adherence in those least likely to attend [ 39 ]. As data on these characteristics have not been commonly collected, then any health inequalities among these characteristics cannot be identified or monitored and improvements cannot be made [ 104 , 109 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collecting and reporting an individual's characteristics in pulmonary rehabilitation studies and audits consistently allows for the monitoring of potential health inequalities and may provide information on differences in the access, completion and outcomes of pulmonary rehabilitation across individuals [ 35 , 36 ]. This information can be used to establish whether services are equitable, fair and accessible for all [ 37 , 38 ] and challenge health inequalities by adapting and improving services [ 38 ], including pulmonary rehabilitation [ 39 ]. Reporting guidelines such as Consolidated Standards of Reporting Trials, Strengthening the Reporting of Observational Studies in Epidemiology and Consolidated Criteria for Reporting Qualitative Research recommend the reporting of “important” characteristics of study participants; however, no specific characteristics are stated [ 40 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional patient education programmes often assume that simply providing information will lead to behaviour change. However, this program recognises a critical limitation that education alone is insufficient [ 35 ] and does not improve exercise performance [ 14 ]. This program explicitly addresses this gap and prioritises fostering awareness and willingness to change alongside knowledge acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…This program explicitly addresses this gap and prioritises fostering awareness and willingness to change alongside knowledge acquisition. Nonetheless, patient education is a crucial component of PR programmes, as it empowers patients with the knowledge and skills to manage their condition effectively and improve their HRQoL [ 35 , 36 ]. .…”
Section: Introductionmentioning
confidence: 99%
“…In England, around 31% of referred COPD patients do not take up their PR appointment, more so from deprived communities 9 , 10 . Systematic reviews have found insufficient high-quality evidence to make clear recommendations for effective interventions to increase uptake 11 , 12 . In a previous study, we identified barriers and enablers to PR uptake at several stages on the PR pathway within and between primary care, PR providers and patients.…”
Section: Introductionmentioning
confidence: 99%